2008
DOI: 10.2169/internalmedicine.47.1061
|View full text |Cite
|
Sign up to set email alerts
|

Lamivudine Treatment Improves the Prognosis of Fulminant Hepatitis B

Abstract: Objective The efficacy of lamivudine for fulminant hepatitis B has been reported in Europe and West Asia. However, in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
55
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 24 publications
4
55
1
3
Order By: Relevance
“…In a systematic review and meta-analysis of five studies, an increased-dose HBV vaccination schedule improved anti-HBs response rates compared to standard-dose HBV vaccination (OR 1.96; 95% CI: 1.47, 2.61) with separate randomised trial data demonstrating improved serological response with four-dose regimens [67][68][69][70][71]. An accelerated course (three doses given at 0, 1 and 3 weeks) of low-dose vaccine was non-inferior to a standard course (three doses given at months 0, 1 and 6) only in those with CD4 counts above 500 cells/μL with no data existing for a similar schedule using double-dose vaccine [72].…”
Section: Rationalementioning
confidence: 99%
See 3 more Smart Citations
“…In a systematic review and meta-analysis of five studies, an increased-dose HBV vaccination schedule improved anti-HBs response rates compared to standard-dose HBV vaccination (OR 1.96; 95% CI: 1.47, 2.61) with separate randomised trial data demonstrating improved serological response with four-dose regimens [67][68][69][70][71]. An accelerated course (three doses given at 0, 1 and 3 weeks) of low-dose vaccine was non-inferior to a standard course (three doses given at months 0, 1 and 6) only in those with CD4 counts above 500 cells/μL with no data existing for a similar schedule using double-dose vaccine [72].…”
Section: Rationalementioning
confidence: 99%
“…Another RCT in monoinfected patients treated with either 3TC or no antivirals for acute severe HBV showed a threefold reduction in liver failure and death in the 3TC arm, although the survivors in the placebo arm were less likely to become chronically infected [67]. Two retrospective case-control studies of monoinfected patients treated with 3TC for fulminant hepatitis B showed a three-fold reduction in mortality in the treated patients, and none of the survivors progressed to chronic infection [68,69].…”
Section: Rationalementioning
confidence: 99%
See 2 more Smart Citations
“…A study 3 detected strong production of protein MxA (a specific marker for IFN signalling) in the inflammatory cells of skin samples of anti-TNF-a-induced psoriasis as compared with controls. Another study 7 found increased IFN-a expression in the psoriatic lesions of patients receiving anti-TNF-a therapy, as compared with spontaneous psoriasis. Furthermore, since the time between anti-TNF-a administration and the development of psoriatic lesions may be extremely variable, 2 an environmental trigger could be involved in this pathophysiological mechanism.…”
mentioning
confidence: 94%